2021
DOI: 10.1111/jce.14989
|View full text |Cite
|
Sign up to set email alerts
|

High‐power, short‐duration atrial fibrillation ablation compared with a conventional approach: Outcomes and reconnection patterns

Abstract: Background: The effectiveness, safety, and pulmonary vein (PV) reconnection patterns of point-by-point high-power, short-duration (HPSD) ablation relative to conventional force-time integral (FTI)-guided strategies for atrial fibrillation (AF) ablation are unknown.Objectives: To compare 1-year freedom from atrial arrhythmia (AA), complication rates, procedural times, and PV reconnection patterns with HPSD AF AF ablation versus an FTI-guided low-power, long-duration (LPLD) strategy. Methods:We compared consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 22 publications
0
32
1
Order By: Relevance
“…Interestingly, utilization of high power‐short duration (HPSD) energy settings seems to be associated with a higher rate of remaining carina conduction. Klein et al 21 reported different reconnection patterns with HPSD (50 W) and force‐time integral guided low‐power long duration (LPDL, 25‐35 W) strategies. Although both groups showed similar freedom of arrhythmia at 1 year (79% vs 73%; P =.339), a higher propensity for reconnection at the right PV carina was found in the HPSD group compared with the LPLD group (46.7% vs 20.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, utilization of high power‐short duration (HPSD) energy settings seems to be associated with a higher rate of remaining carina conduction. Klein et al 21 reported different reconnection patterns with HPSD (50 W) and force‐time integral guided low‐power long duration (LPDL, 25‐35 W) strategies. Although both groups showed similar freedom of arrhythmia at 1 year (79% vs 73%; P =.339), a higher propensity for reconnection at the right PV carina was found in the HPSD group compared with the LPLD group (46.7% vs 20.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have shown that high power, short duration ablation was safe, reduced total procedure time, and achieved comparable long‐term efficacy in AF recurrence 22‐25 . In recently published data, high power short duration ablation using 50 W/8‐10 seconds in anterior and 50 W/6‐8 seconds in posterior showed similar 1‐year AF‐free survival rate and shorter procedure times compared to conventional power FTI‐guided ablation in PVI 26 . This recent study did not apply real‐time AI or LSI estimation during ablation.…”
Section: Discussionmentioning
confidence: 97%
“…However, applying 50 W in 5 seconds showed variable FTI or lesion index (LSI) values according to CF: mean FTI varied from 47 to 376 g*seconds and mean LSI varied from 4.1 to 7.6 25 . Also, high power short duration ablation showed a higher propensity for reconnection of the right PV carina compared to conventional power ablation 26 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations